Linearity of the Academic Career in Accounting Sciences: An Essay Focusing on Liquid Modernity - Lopes, Iago; Colauto, Romualdo Douglas (Advances in Scientific and Applied Accounting, 2025)
Objective: To reflect on the aspects inherent to the academic career in accounting, framed within Liquid Modernity, that have altered the development of this career from a linear system to a non-linear system. Method: A research with an essayistic character, with a constructionist approach. Results and Discussions: Careers respond to the emancipation and individuality of the subject. Employer organizations and/or occupational spaces represent one of the demographic domains that individuals rely on to construct their academic career. Careers can be viewed as a life story composed of unique, multiple, and individual experiences. We are faced with a community, in which the university is included, characterized by the temporary permanence of individuals who are building their careers within non-linear systems. Contributions: This research contributes to the diffusion of Bauman’s ideas in traditional fields of knowledge, such as accounting, and provides insights into the practice of perpetuating the choice of an academic career by individuals embedded in Liquid Modernity.